The Analysis on Chinese Traditional Ideology’s Impacts on Aged People’s Motivation to Continue Working - Yu, Rongrong (2017)
This paper examines Chinese employees' acceptance and considerations towards bridge employment. Bridge employment provides retirees opportunities to continue working after retirement. It seems that bridge employment has become broadly accepted by individuals in some developed countries. However, Chinese older workers show much resistance towards it. This research is based on 157 quantitative data collected through questionnaires. Through analyzing cross-tables, this survey shows that the traditional ideology regarding inter-generational connection still exists and plays an influential factor in the decision-making process of bridge employment acceptance. Besides, other individual factors and organisational factors are also examined.